The potential of Rhipicephalus microplus as a vector of Ehrlichia ruminantium in West Africa - Some, M.V.; Biguezoton, A.S.; Githaka, Naftaly W.; Adakal, H.; Dayo, G.-K.; Belem, A.; Zoungrana, S.; Stachurski, F.; Chevillon, C. (Elsevier, 2023)
Heartwater, or cowdriosis, is a virulent tick-borne rickettsial disease of ruminants caused by Ehrlichia ruminantium, biologically transmitted by Amblyomma species (A. variegatum in West Africa). In West Africa, this bacterium was recently reported to naturally infect the invasive cattle tick, Rhipicephalus microplus (Rm) through trans-ovarian transmission from replete adult females to offspring. A ‘sheep-tick-sheep’ cycle was set up to determine whether feeding the progeny of these ticks on naïve sheep could lead to infection, and to compare clinical outcomes resulting from this transmission with those observed following infection by the natural A. variegatum (Av) vector. Using local strains of ticks (KIMINI-Rm and KIMINI-Av) and of E. ruminantium (BK242), we recorded, using the PCR technique, the presence of bacterial DNA in ticks (larvae for Av and females for Rm) engorged on sheep inoculated by BK242-infected blood. The bacterial DNA was also detected in the next stages of the lifecycle of R. microplus (eggs and larvae), and in sheep infested either by those R. microplus larvae or by A. variegatum nymphs moulted from larvae engorged on blood-inoculated sheep. Bacterial infection in these sheep was demonstrated by detecting antibodies to E. ruminantium using the MAP1-B ELISA and by isolation of the bacterium on cell culture from blood. The sequences of PCS20 gene detected in ticks and sheep were identical to that of the BK242 strain. Our results confirm that R. microplus can acquire and transmit E. ruminantium to the next stage. However, this transmission resulted in a mild subclinical disease whereas severe clinical disease was observed in sheep infested by A. variegatum infected nymphs, suggesting differences in the tick/bacteria relationship. Future studies will focus on replicating these findings with ticks of different isolates and life stages to determine if R. microplus is playing a role in the epidemiology of heartwater in West Africa. Additionally, studies will investigate whether sheep that are seropositive due to infestation by E. ruminantium-infected R. microplus are subsequently protected against heartwater. Such data will add to our understanding of the possible impact of R. microplus in areas where it has become recently established.